If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 7 = 2 Reorder the terms: 7 + -2x = 2 Solving 7 + -2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 2 + -7 -2x = 2 + -7 Combine like terms: 2 + -7 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| (x^4)-(12x^2)+(11)=0 | | 0.5y+1=4x-2 | | 2x-5y=28 | | -5(x+4)=7-(-5) | | (3+2i)(4+3i)= | | -3x+8=2x+3 | | (3/y)+(2/5)=19/20 | | 6x^2+4x=21 | | -7(2x+8)=14 | | 8z+22=3(3z+11)z | | 11x-3x=400 | | (x^4)-(5x^2)+(4)=0 | | 6(2/3x-7/6)=6*7/2 | | -2y-1=4x+3 | | b+9=24 | | 23x=173 | | 4(x+19)=3x+41 | | y=-4y+1 | | 2(-.26)+7.5=6.2-3(-.26) | | 13x+21=47 | | 3a+7b=1650 | | f(t)=2.25+0.75x | | 4+x=4x-23 | | 0.2c-0.6+.5c=5 | | 3(6+8)=24+18x | | 10m^2-6=404 | | -11.1-2.2x=2.2x/7.7-2x-x^2 | | x^3+5x^2-5x-25=0 | | 1x-2=6x+5 | | (3a+19)+2z= | | 5w+2=w+10 | | x-200=.2x |